Brazil’s COVID-19 Epicenter in Manaus: How Much of the Population Has Already Been Exposed and Are Vulnerable to SARS-CoV-2? - Fearnside, Philip Martin; Tupinambás, Unaí; Vassão, Ruth Camargo; Leão, Jeremias; Almeida, Alexandre C.L.; Steinmetz, Wilhelm Alexander; Duczmal, Luiz Henrique; Ferrante, Lucas (Journal of Racial and Ethnic Health Disparities, 2021)
Is Brazil’s COVID-19 epicenter really approaching herd immunity? A recent study estimated that in October 2020 three-quarters of the population of Manaus (the capital of the largest state in the Brazilian Amazon) had contact with SARS-CoV-2. We show that 46% of the Manaus population having had contact with SARS-CoV-2 at that time is a more plausible estimate, and that Amazonia is still far from herd immunity. The second wave of COVID-19 is now evident in Manaus. We predict that the pandemic of COVID-19 will continue throughout 2021, given the duration of naturally acquired immunity of only 240 days and the slow pace of vaccination. Manaus has a large percentage of the population that is susceptible (35 to 45% as of May 17, 2021). Against this backdrop, measures to restrict urban mobility and social isolation are still necessary, such as the closure of schools and universities, since the resumption of these activities in 2020 due to the low attack rates of SARS-CoV-2 was the main trigger for the second wave in Manaus. © 2021, W. Montague Cobb-NMA Health Institute.
Keywords: Herd immunity; Coronavirus